2022
DOI: 10.3390/pharmaceutics14061204
|View full text |Cite
|
Sign up to set email alerts
|

Modern Dressings in Prevention and Therapy of Acute and Chronic Radiation Dermatitis—A Literature Review

Abstract: Radiotherapy is an integral part of modern oncology, applied to more than half of all patients diagnosed with cancer. It can be used alone or in combination with surgery or chemotherapy. However, despite the high precision of radiation delivery, irradiation may affect surrounding healthy tissues leading to the development of toxicity. The most common and clinically significant toxicity of radiotherapy is acute and chronic radiation dermatitis, which could result in desquamation, wounds, nonhealing ulcers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The material’s flexibility enables the film to conform to complex shapes while facilitating gas exchange, which has been proven to promote healing [ 34 ]. Additionally, its transparency allows for the close monitoring of the wounded area without removing the film, thereby reducing trauma during dressing changes, minimizing exposure to bacteria, and lowering the risk of infection by up to one week [ 34 , 35 ].…”
Section: Polymeric Films For Wound Healingmentioning
confidence: 99%
“…The material’s flexibility enables the film to conform to complex shapes while facilitating gas exchange, which has been proven to promote healing [ 34 ]. Additionally, its transparency allows for the close monitoring of the wounded area without removing the film, thereby reducing trauma during dressing changes, minimizing exposure to bacteria, and lowering the risk of infection by up to one week [ 34 , 35 ].…”
Section: Polymeric Films For Wound Healingmentioning
confidence: 99%
“…In fact, it shows that although rhEGF cannot counteract and reverse the skin reaction caused by radiation dose, it could relieve the pain of radiotherapy and accelerate the healing of skin to some extent. Besides, different types of dressing have been shown as effective ways to prevent and treatment of radiation dermatitis [22]. A combination between rhEGF and dressing may be an efficient treatment, which could be studied in further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A study utilizing thermal radiation dressings to heat both normal skin on human thighs and surgical wounds (set at 38°C for 2 hours of heating followed by 2 hours of rest, over a period of 7 days) maintained wound temperatures between 36.0-37.5°C. 65 This demonstrated that local heating can enhance microvascular blood flow and subcutaneous oxygen content in both normal and injured skin, potentially offering resistance to infection without increasing collagen deposition at the wound site. In addition, thermal radiation dressings (set at 38°C, three times a day for 1 hour) were used for the treatment of Stage I-II uninfected pressure injuries over 6 weeks or until healing showed that, compared to standard treatment with alginate dressings, this method significantly improved wound healing rates.…”
Section: Pressure Injurymentioning
confidence: 97%